1983
DOI: 10.1177/0310057x8301100308
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion and Cerebral Protection during Carotid Endarterectomy

Abstract: The relative sajety oj carotid endarterectomy depends upon surgical expertise combined with appropriate monitoring oj cerebral perjusion and the ability to intervene either surgically or pharmacologically to match cerebral perjusion to cerebral oxygen requirement. Methods oj monitoring adequacy oj cerebral perjusion are reviewed and include regional cerebral blood jlow measurements, electroencepha/ographic monitoring, carotid stump pressure measurements, jugular venous oxygen partial pressure, neurological ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the only randomized controlled human trial to date, Nussmeier et al showed a decrease in neuropsychiatric impairment in patients who had EEG burst suppression induced by thiopentone prior to warm cardiopulmonary bypass for cardiac surgery 10 . Two large prospective series have reported good results using thiopentone titrated to burst suppression in place of bypass shunting for CEA 11,12 . Frawley et al reported a stroke rate of 1.7% in 621 patients treated this way 12 and later in the same series a stroke rate of 1.2% in 259 patients with associated contralateral carotid stenosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In the only randomized controlled human trial to date, Nussmeier et al showed a decrease in neuropsychiatric impairment in patients who had EEG burst suppression induced by thiopentone prior to warm cardiopulmonary bypass for cardiac surgery 10 . Two large prospective series have reported good results using thiopentone titrated to burst suppression in place of bypass shunting for CEA 11,12 . Frawley et al reported a stroke rate of 1.7% in 621 patients treated this way 12 and later in the same series a stroke rate of 1.2% in 259 patients with associated contralateral carotid stenosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to restore cortical EEG to precross-clamp status with hypertensive therapy would prompt the initiation of pharmacological burst-suppression for neuroprotection while avoiding intraluminal shunting altogether. 48 Evidence supporting this approach is mostly based on large case series. [49][50][51][52][53][54] To date, there has been no prospective randomized study to compare the efficacy of pharmacological burst-suppression in preventing perioperative stroke to routine shunting and/or selective shunting in the setting of CEA, although these case series have www.anesthesia-analgesia.org…”
Section: Cerebral Protection In Carotid Surgerymentioning
confidence: 99%
“…They have displayed beneficial cerebral effects while performing CEA without adverse cardiovascular outcomes (63,64). They reduce oxygen demand throughout relative tissue ischemia induced by arterial clamping (65,66). Thiopentone has also been demonstrated to provide cerebral protection during CEA and intracranial aneurysm clipping (67).…”
Section: Barbiturate Infusionmentioning
confidence: 99%